2016
DOI: 10.1007/s00038-015-0782-8
|View full text |Cite
|
Sign up to set email alerts
|

Reluctance to seek professional help among suicidal people: results from the Swiss Health Survey

Abstract: Objective: To investigate whether help-negation (not accepting or accessing available helping resources) among suicidal people can also be found in a Swiss sample. Methods: Data on 16640 participants (aged 15 and older) from the Swiss Health Survey 2012 was analyzed. Logistic regression analyses were conducted to study the association between suicidality (categorized into "not at all"; "several days"; and "more than half of the days") and currently being in treatment for depression (covariates: depression and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In Na et al’s ( 58 ) study, greater age was found to be associated with a less favorable attitude toward suicide which may interfere help-seeking. The effect of age was also identified in research conducted by Dey and Jorm ( 55 ) but varied by gender. Specifically, men in the age groups of 45–54 and 55–64 were more likely than those 75 or older to be in treatment, whereas middle-aged females (35–64 years old) were at greater odds of getting treatment compared to those aged 15–24.…”
Section: Resultsmentioning
confidence: 57%
See 3 more Smart Citations
“…In Na et al’s ( 58 ) study, greater age was found to be associated with a less favorable attitude toward suicide which may interfere help-seeking. The effect of age was also identified in research conducted by Dey and Jorm ( 55 ) but varied by gender. Specifically, men in the age groups of 45–54 and 55–64 were more likely than those 75 or older to be in treatment, whereas middle-aged females (35–64 years old) were at greater odds of getting treatment compared to those aged 15–24.…”
Section: Resultsmentioning
confidence: 57%
“…Non-Hispanic Whites were also more likely to use services for suicide ideation (odds ratio [OR] = 2.11), suicide plan (OR = 2.39), and suicide attempt (OR = 2.95) compared to Black, Hispanic, and other groups in Stanley et al’s study ( 54 ). Finally, in Dey and Jorm’s study ( 55 ), a higher percentage of non-Swiss participants indicated experiencing suicidality on more than half of the days in the reporting period, and non-Swiss females were at lower odds to be in treatment compared to Swiss females.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Inadequate treatment can thereby produce a ripple effect wherein affected individuals may lose faith in the mental health system as effective, thereby reducing the likelihood that they would seek treatment from an alternative provider who may be able to provide effective care or recommend treatment to others in the future. Help-negation is already a significant problem for suicidal individuals (Dey & Jorm, 2016), and exposure to inadequate treatment may further reduce the likelihood of help-seeking and increase stigma and hopelessness. Given that many public health approaches to suicide prevention culminate in referring at-risk individuals to treatment, a situation that is already anxiety-provoking enough for suicidal individuals and their impacted friends and family, it is critical that the clinicians receiving these referrals be competent.…”
Section: Discussionmentioning
confidence: 99%